PRAGMATIC ANALYSIS OF ONLINE CARTOONS OF THE 2023 PRESIDENTIAL ELECTION IN NIGERIA - Alyebo , Nelson Orkaan; Zayol, Meshach Terfa (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
Linguistic studies have shown that meaning is derived from utterances through cartoons. Before and during the 2023 presidential elections, the internet and public space were inundated with cartoons intended by the cartoonists to satirize targeted presidential aspirants. The leading contenders in the elections were Asiwaju Bola Ahmad Tinubu, Alhaji Atiku Abubakar and Peter Obi. They were heavily cartooned. While Tinubu led with Emi Lokan (my turn), Batist, Batified, and Batism; Atiku Abubakar with Articulated, Peter Obi did with Obident Movement. Both of these politicians were represented through cartoons, by those against their candidatures or just cartoon enthusiasts. There are cartoonists who represented them in a manner, tone, and language that made them appear not to be worth heaping even with cow dung. This study therefore analyses the different functions of these cartoons in relation to context, cartoon characters, intentions, world knowledge, implicatures, and mutual contextual beliefs. This study analyses the online cartoons through the lenses of Pragma-crafting Theory as a broad and systematic instrument for the explicit and valid pragmatic analysis of texts. The findings of the study reveal that there are latent meanings in the cartoons which transcend sentence meanings and sketched images. The findings also reveal that the intentions, attitudes, expectations, the context in which the cartoons are used and the targets cartooned leave definite impressions on the minds of the readers and viewers.